Table of Contents: Life Science 13 (2) 2024 - Life Science (Universitas Negeri Semarang, 2024)
Life Science Edition 13 (2) 2024 consists of 9 articles which fall within the scope of microbiology, zoology, botany and ecology. Articles were written by academics from 3 university, such as Universitas Negeri Semarang, Universitas Diponegoro, and Universitas Tanjungpura.